Illusion space: Exploration and application of projection mapping technology in spatial design - Wang, Yu (My University, 2022)
In this era of rapid development of various technologies, architects are seeking more diverse approaches as other professions. In The Second Digital Turn, Mario Carpo pointed out that variability is a deep-rooted ambition of architects and designers, and the design professions are now coming to terms with a new kind of digital tools they have adopted—no longer tools for making but tools for thinking (Carpo, 2017). In this context, the thesis explores transformations that new technologies can bring to architecture design and try to expand the boundaries of the architectural discipline. This thesis discusses how projection mapping technology may affect the architectural design process. The general principles of projection mapping are summarized through case studies, and these principles are used as the basics of the design experiments. With the method of research by design, the design experiments are used as the main tool to explore the interaction between physical objects and virtual projection, as well as to simulate the spatial effects that projections can achieve speculatively. These effects were eventually applied to an Immersive theater design where the audience can follow the actors in a sequence of space to experience the narratives of the classic Kurosawa film Rashomon. In this theater, different scenes can be represented in the same physical space through projection mapping, the limited space can be extended, non-existent objects can be created, and the shape of the space can be changed according to the demand. There are two lines of design method in this thesis: one is the design of the physical environment that will be projected, and the other is the design of the virtual projection content. The combination of projected images and the physical environment is the main focus of the design, and the architect controls the boundary and relationship between real and virtual. In this thesis, the design experiments and immersive theater design parts have an equally important place in the outcome, because the exploration and application of the possibility of projection mapping technology is the main goal of this thesis.
Keywords: The second digital turn; Spatial augmented reality; Projection mapping; Immersive theater